Digital Transformation as a Strategy for Building Adaptive Pesantren Management Systems - Fitra Putri Oganda; Po Abas Sunarya; Marviola Hardini; Sondang Visiana Sihotang; Ramiro Santiago Ikhsan; Maulana Abbas (ADI Publisher, 2025)
Digital transformation has become a central force in reshaping the educational ecosystem in the era of Industry 4.0. In Islamic education, particularly within pesantren, digitalization plays a strategic role in improving digital literacy, promoting social inclusion, and strengthening community engagement. This study aims to examine how digital transformation can be effectively implemented in pesantren management through adaptive strategies that integrate technology, learning innovation, and organizational governance. A qualitative approach was used, with data collected from 30 in-depth interviews involving educators, students, pesantren administrators, parents, and educational technology experts. Additional data were obtained through 3–5 observations of digital activities, internal documentation, and a review of 25–40 relevant academic sources. Data analysis was conducted through data reduction, thematic categorization, and triangulation across interviews, observations, and documentation. The findings show that digital transformation enables pesantren to enhance management adaptability, improve learning experiences, and strengthen collaboration with external stakeholders. The success of these digital initiatives is influenced by leadership commitment, human resource readiness, and community participa- tion. The study also highlights that digital literacy programs support students’ preparedness for an increasingly technology-driven global environment. This study contributes to the discourse on digital education in Islamic institutions by offering practical insights for policymakers and pesantren leaders in balancing tradition with innovation, emphasizing the need for strategic planning and capacity development to ensure sustainable and mission-aligned digital practices.